(untitled) (Research, Society and Development, 2022)
Randomized clinical trials are considered the gold standard of studies to assess the efficacy and safety of clinical interventions such as experimental drugs, health products and/or therapeutic procedures. This is an integrative literature review was developed to identify the importance of the bioethical principle of autonomy in conducting research and clinical trials. Due to its importance in accessing new technologies in the field of health and the challenges related to its adequacy to bioethics principles, the present study aimed to carry out a survey of how this aspect is being addressed. The selected research show investigations and discussions of elements that can compromise and influence individuals’ freedom of choice in clinical studies and their opinion about the problems. We conclude that, of the bioethics principles, autonomy is the most likely to be negatively affected in clinical trials, demonstrating the importance of bioethics in identifying gaps and establishing limits between advances in medical research and ethical and moral values.